2013
DOI: 10.1096/fj.12-225961
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of protein S by platelet kinases enhances its activated protein C cofactor activity

Abstract: Protein S (PS) is a multifunctional plasma protein of the hemostatic and inflammatory pathways, although mechanisms for its regulation are poorly understood. Since certain plasma proteins are regulated through extracellular phosphorylation, we investigated whether the anticoagulant activity of PS is regulated through phosphorylation by platelet-secreted kinases. PS was phosphorylated on exposure to activated platelets or their releasates, as judged by immunoblotting for phospho-amino acids and PS. PS phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Protein kinase activities in the form of protein kinase A (PKA) (93), several isoforms of protein kinase C (PKC) (115), and casein kinases 1 and 2 (CK1 and CK2) (98–100, 102, 103, 107115) have all been identified in the releasate from activated platelets. They have all been shown to mediate extracellular phosphorylation of specific plasma proteins, in particular proteins within the cascade systems, provided that ATP and Ca 2+ are present in sufficient amounts.…”
Section: Platelet-mediated Extracellular Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein kinase activities in the form of protein kinase A (PKA) (93), several isoforms of protein kinase C (PKC) (115), and casein kinases 1 and 2 (CK1 and CK2) (98–100, 102, 103, 107115) have all been identified in the releasate from activated platelets. They have all been shown to mediate extracellular phosphorylation of specific plasma proteins, in particular proteins within the cascade systems, provided that ATP and Ca 2+ are present in sufficient amounts.…”
Section: Platelet-mediated Extracellular Phosphorylationmentioning
confidence: 99%
“…Furthermore, it has been suggested that anticoagulation is regulated by platelet-mediated phosphorylation: Coagulation factor Va becomes more readily inactivated by activated protein C after phosphorylation by platelet casein kinase (128). More recently, platelet-secreted casein kinase(s) have been shown to phosphorylate protein S, thereby enhancing its activated protein C cofactor activity (103). In that publication, the authors postulated that extracellular platelet-mediated phosphorylation of protein S is a previously unrecognized mechanism for regulating its anticoagulant activity, and that role of phosphorylation most likely applies to all the substrates discussed here.…”
Section: Platelet-mediated Extracellular Phosphorylationmentioning
confidence: 99%
“…Previous studies have identified in vitro phosphorylation of extracellular plasma proteins such as fibrinogen, complement protein C3, vitronectin, factor V and protein S by kinases, including casein kinase 1, casein kinase 2, protein kinase C and protein kinase A . However, these kinases are predominately localized in the cytoplasm and/or nucleus and not likely to encounter extracellular proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Свободный протеин S имеет два механизма антикоагулянтного влияния. С од-ной стороны, активация тромбоцитов сопровождается выделением ими киназ, которые сразу же усиливают фосфорилирование свободного протеина S и тем самым повышают в 1,5-2,0 раза его кофакторную активность к протеину С [32]. Фосфорилированный протеин S об-ладает высоким сродством к отрицательно заряженным фосфолипидам и тем самым улучшает контакт активи-рованного протеина С с мембраной за счет образова-ния комплекса с ним.…”
Section: Discussionunclassified